Navigating the Therapeutic Landscape of Head and Neck Burkitt’s Lymphoma: A Comparative Analysis of Treatment Approaches and Associated Challenges - Ali Eltair (AlQalam Journal of Medical and Applied Sciences, 2025)
Head and neck Burkitt lymphoma (HN-BL) requires tailored treatment strategies due to its unique anatomical location and aggressive nature. HN-BL poses distinctive diagnostic and therapeutic obstacles in contrast to its extranodal equivalents. This review comparatively analyzes current treatment approaches for HN-BL, including intensive chemotherapy regimens, radiation therapy strategies, and the emerging role of targeted therapies. We investigate the effectiveness and adverse effect profiles of these methodologies, emphasizing determinants that affect treatment choice including neoplasm stage, patient functional capacity, and the existence of comorbid conditions. Furthermore, the abstract discusses challenges in managing treatment-related complications, achieving optimal local control, and addressing the specific anatomical challenges posed by head and neck involvement. Finally, we explore areas requiring further investigation to improve outcomes and refine therapeutic strategies for this aggressive malignancy. يتطلب سرطان الغدد الليمفاوية البُركيتي في الرأس والعنق استراتيجيات علاجية مُخصصة نظرًا لموقعه التشريحي الفريد وطبيعته العدوانية. يطرح سرطان الغدد الليمفاوية البُركيتي في الرأس والعنق تحديات تشخيصية وعلاجية مميزة مقارنةً بنظائره خارج العقد الليمفاوية. تستعرض هذه المراجعة بشكل مُقارن الأساليب العلاجية الحالية لـسرطان الغدد الليمفاوية البُركيتي في الرأس والعنق ، بما في ذلك نظم العلاج الكيميائي المكثفة، واستراتيجيات العلاج الإشعاعي، والدور الناشئ للعلاجات الموجهة. كما نبحث في فعالية هذه المنهجيات وملامح الآثار الجانبية لها، مع التركيز على المحددات التي تؤثر في اختيار العلاج، بما في ذلك مرحلة الورم، والقدرة الوظيفية للمريض، ووجود الظروف المرضية المصاحبة. علاوة على ذلك، يناقش الملخص التحديات في إدارة المضاعفات المرتبطة بالعلاج، وتحقيق السيطرة الموضعية المثلى، ومعالجة التحديات التشريحية الخاصة التي يفرضها إصابة الرأس والعنق. أخيرًا، نستكشف المجالات التي تتطلب مزيدًا من البحث لتحسين النتائج وصقل الاستراتيجيات العلاجية لهذا الورم الخبيث العدواني. الهدف من هذه الدراسة هو جراء مراجعة شاملة ومقارنة لفعالية أساليب العلاج المختلفة لسرطان الغدد الليمفاوية البُركيتي في الرأس والعنق، وملامح السمية المرتبطة بها، والتحديات المصاحبة لها، وتحديد المجالات التي تتطلب إجراء أبحاث مستقبلية وتحسين الاستراتيجيات العلاجية. الأثر المتوقع هو تعزيز المعرفة الأساسية لتوجيه عملية صنع القرار السريري، وتعزيز الابتكار، وفي نهاية المطاف، تحسين النتائج السريرية عن طريق التحكم في النفقات في تقديم الرعاية الصحية